The Legal Status of the Environmental Refugee - Hamoud, Sabrina; Khalfa, Nadia (Journal of Legal Studies and Researches, 2021)
Environmental refugee is a relatively new term that has been of migration has become one of the most important security threats to introduced to the global arena in light of climate changes, and this type human survival and the preservation of his existence, despite the fact that the environment is from time immemorial one of the most important factors that contribute to determining man’s choices about what It depends on where he lives.